The Singapore Convention on Mediation a commentary - Alexander, Nadja Marie, 1966- (Global trends in dispute resolution, 2022)
The Singapore Convention on Mediation is just beginning its life as an international legal instrument. How is it likely to fare? In this first comprehensive, article-by-article commentary, the authors provide a robust report on the features of the Convention and their implications, with analysis of potential controversies and authoritative clarifications of particular provisions.